Pengaruh Website E-Commerce Dan Kualitas Produk Terhadap Loyalitas Melalui Kepuasan Konsumen Sebagai Variabel Intervening dan Prespektif Ekonomi Islam (Studi Kasus Mahasiswa UIN Sumatera Utara) - Dewi Berlian Harahap; M. Ridwan; Nur Ahmadi Bi Rahmani (ITB AAS INDONESIA Surakarta, 2023)
E-commerce business actors need to pay more attention to the level of consumer satisfaction which will ultimately lead to consumer loyalty. The relationship between loyalty and satisfaction is even stronger in the online environment than in the offline environment. The research used is quantitative method. The results show that e-commerce websites have no significant effect on customer satisfaction, product quality has a significant effect on customer satisfaction, customer satisfaction has a significant effect on loyalty, e-commerce websites have no significant effect on loyalty, product quality has a significant effect on loyalty, e-commerce websites have no significant effect on loyalty. commerce has no significant effect on loyalty through customer satisfaction and product quality has a significant effect on loyalty through customer satisfaction. E-commerce application transactions include a legitimate business system, and there are elements of injustice in transactions according to sharia economic principles.